Identification Of Aquatic Plant Species From Bantimurung Waterfall And Their Phytochemical Compounds Analysis - Nugraha, Media Fitri Isma; Maharani, Fasya Hadaina; Novita, Hessy; Rajamuddin, Muh Alias L; Yunita, Rossa; Reflinur, Reflinur; Enggarini, Wening; Julzarika, Atriyon; Elya, Berna Elya (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2019)
A total of 21 aquatic plant species were collected from Bantimurung waterfall areas, South Sulawesi, Indonesia, in October 2017. These plant materials were subjected to both species and phytochemicals identification. The aims of this study were to determine the species or taxonomic rank of Indonesian aquatic plants collected from Bantimurung waterfall, South Sulawesi, Indonesia and to identify their chemical compounds (phytochemicals) as a candidate for new herbal medicine. Plant genetic materials used in this study were collected from Bantimurung Bulusaraung waterfall and were then identified based on standard botanical techniques for species identification in the Herbarium Bogoriense, Research center for Biology Indonesian Institute of Science (LIPI), Cibinong, West Java. The samples were subjected to the phytochemistry screening such as alkaloids, flavonoids, tannins, saponins, glycosides, terpenoids and anthraquinone followed the procedures of Indonesian Materia Medika and Harborne. Results showed that all collected aquatic plant samples were able to be identified, including their species names. Phytochemical screening of each sample revealed the presence of glycoside in all of the tested species. However, no alkaloids, anthraquinones, and terpenoids were observed in those tested plant samples. Of the total 21 aquatic plants, 14 species contained flavonoids, 8 species contained phenol compound, and 10 species contained saponins. Among these species Donnax canniformis possessed good antioxidant activity, which correlated to its total phenolic and flavonoid contents. Our results would be beneficial for any future effort in the development of new herbal drugs derived from aquatic plants.